Lipidomics reveals similar changes in serum phospholipid signatures of overweight and obese pediatric subjects - Anjos, Sara (2019)
Obesity is a public health problem and a risk factor for pathologies such type 2 diabetes mellitus, cardiovascular diseases, and nonalcoholic fatty liver disease. Given these clinical implications, there is a growing interest to understand the pathophysiological mechanism of obesity. Changes in lipid metabolism have been associated with obesity and obesity-related complications. However, changes in the lipid profile of obese children have been overlooked. In the present work, we analyzed the serum phospholipidome of overweight and obese children by HILIC-MS/MS and GC-MS. Using this approach, we have identified 165 lipid species belonging to the classes PC, PE, PS, PG, PI, LPC, and SM. The phospholipidome of overweight (OW) and obese (OB) children was significantly different from normal-weight children (control). Main differences were observed in the PI class that was less abundant in OW and OB children and some PS, PE, SM, and PC lipid species are upregulated in obese and overweight children. Although further studies are needed to clarify some association between phospholipid alterations and metabolic changes, our results highlight the alteration that occurs in the serum phospholipid profile in obesity in children.